Qualitative perspectives on gesture in saxophone performance: two case studies - Moura, Nádia (2020)
The increasing research on gesture in music performance demon- strates its influence embraces technical, expressive and communi- cative dimensions, which mastery is essential to the achievement of skilled, meaningful musical presentations. This study constitutes a preliminary exploration of gesture-making in the specific case of saxophone performance, framed on a larger on-going research cen- tered in understanding the role of gesture and the ways it can im- prove pedagogy and playing. An analysis of two video recordings of renowned contemporary saxophonists and pedagogues interpret- ing the same repertoire was conducted through a systematic obser- vation procedure previously applied to other instruments. Whilst each artist had a personal way of communicating through his gesture vocabulary, common features amongst saxophonists (and other wind instrumentalists) were extracted. Findings permitted to establish a set of gesture types related to saxophone performance, as well as expand on their functional nature and correlation with the musical content.